1995
DOI: 10.1111/j.1365-2761.1995.tb00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Residues of [14C]‐malachite green in eggs and fry of rainbow trout, Oncorhynchus mykiss (Walbaum), after treatment of eggs

Abstract: Rainbow trout, Oncorhynchus mykiss (Walbaum), eggs were exposed to [methano-''*C] malachite green chloride on day 0 and on every third day thereafter through day 24, with a final treatment administered to fry on day 31. Eggs or fry were sampled before each treatment, and at selected times from day 31 to day 59. Malachite green equivalence in eggs and fry was determined by sample oxidation and liquid scintillation counting. Total malachite green residues increased throughout the exposure period to 0-271+0-042/Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 10 publications
0
15
0
2
Order By: Relevance
“…Law (1994) reported on the metabolism of MG and LMG in fingerling trout exposed to 2 mg l −1 for 1 h. The MG in whole fish homogenates decreased with time, while LMG increased up to 24 h after exposure and remained steady for the next 7 days. Meinertz et al (1995) determined the amount of MG residue in eggs and fry after an egg exposure at 1 μg ml −1 on day 0 and on every third day through day 24, with a final treatment administered to fry on day 31. The concentration of MG residue (µg g − 1 ) on day 31 was 0.271 μg g − 1 and declined monoexponentially with a half-life of 9.7 days.…”
Section: Introductionmentioning
confidence: 99%
“…Law (1994) reported on the metabolism of MG and LMG in fingerling trout exposed to 2 mg l −1 for 1 h. The MG in whole fish homogenates decreased with time, while LMG increased up to 24 h after exposure and remained steady for the next 7 days. Meinertz et al (1995) determined the amount of MG residue in eggs and fry after an egg exposure at 1 μg ml −1 on day 0 and on every third day through day 24, with a final treatment administered to fry on day 31. The concentration of MG residue (µg g − 1 ) on day 31 was 0.271 μg g − 1 and declined monoexponentially with a half-life of 9.7 days.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, removal of dead eggs leads to a higher hatching rate and higher juvenile survival. A variety of antifungal agents (formaldehyde, malachite green, hydrogen peroxide, isopropyl alcohol, copper sulphate, potassium permanganate and iodine) have already been tested on astacid crayfish eggs, but proved inefficient for regular use due do toxic characteristics for humans and/or eggs (formaldehyde, potassium permanganate, malachite green, iodine) (Meinertz et al 1995;Celada et al 2004;Sáez-Royuela et al 2009) or showed no antifungal effects (isopropyl alcohol, copper sulphate, hydrogen peroxide) (Celada et al 2004;Melendre et al 2006). Formaldehyde showed good effectiveness at high concentrations (Sáez-Royuela et al 2009) but would not be an option due to its reported harmful reproductive and developmental toxicities, including chromosome and DNA damage (Duong et al 2011) especially under eight degrees Celsius.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In the aquaculture industry, saprolegniasis has been controlled effectively with malachite green, although recent studies have shown this compound to be environmentally toxic. [6][7][8][9][10][11][12] Research conducted over the past two decades has reported mutagenic, teratogenic and residual unfavorable activities of malachite green leading to its ban in many countries. [7][8][9][10][11][12] A broad-spectrum bactericide substance known as bronopol has been used for preventing saprolegniasis outbreak in salmon and trout eggs populations.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Research conducted over the past two decades has reported mutagenic, teratogenic and residual unfavorable activities of malachite green leading to its ban in many countries. [7][8][9][10][11][12] A broad-spectrum bactericide substance known as bronopol has been used for preventing saprolegniasis outbreak in salmon and trout eggs populations. However, due to its broad bioactivity 13 and demonstrated toxicities against environmental zooplankton and phytoplankton, bronopol products must be heavily diluted before being discarded, thus increasing usage costs significantly.…”
Section: Introductionmentioning
confidence: 99%